Effects of in situ TiC dispersion and test parameters on the dry sliding wear behaviour of aluminium bronze. (10th May 2019) - Rathod, S; Srivastava, Yogesh; Kiragi, Vinayaka R; Patnaik, Amar
Abstract: In this present investigation, Al-bronze with fine (1–5 μ m) TiC dispersoids containing 5 and 10 wt% were synthesized by self-propagating high-temperature synthesis process followed by casting route. The influence of TiC content in the Al-bronze matrix and test parameters such as applied load and sliding speed on the wear behavior was investigated. The microstructural examination clearly demonstrated that the distribution of TiC dispersoids were fairly uniform in Al-bronze matrix. The presence of α -Cu, β 'and δ phases in the Al-bronze matrix was observed. Results also showed that as the TiC content was increased from 5 to 10 wt% hardness increased from 205 ± 3 to 266 ± 4 and density reduced from 7.25 g cm −3 to 7.1 g cm −3 respectively. Al-bronze-TiC composites showed better wear resistance as compared to the base Al-bronze alloy before reaching a transition load, beyond which the trend reversed. Further, increasing TiC content from 5 to 10 wt% led to an increase in the wear resistance of the composite at 1 m s −1 speed up to a transition load 125 N and at higher speeds remain less than 5 wt% TiC composite. Seizure pressure decreased with increasing TiC content and speed. Operating material removal mechanisms were observed to be adhesion associated with abrasion. The adhesion dominates at higher loads and speeds while abrasion becoming significant at lower speeds and loads. Fragmented TiC particles were suggestive of these operating wear mechanisms. The interfacial cracking at TiC-matrix was also observed to contribute to material removal.